Compassion Integration Within Love Based Curricula Forms Elementary Madrasah Student Character: Integrasi Kasih Sayang Dalam Kurikulum Berbasis Cinta Membentuk Karakter Siswa Madrasah - Mufidah, Arsita Al; Maghfiroh, Lailatul; Nafisah, Aisyah Durrotun (Academia Open, 2026)
General Background Character education in primary schooling requires the foundational development of moral and emotional traits rather than solely focusing on cognitive skills. Specific Background Modern globalization presents social challenges such as selfishness, a lack of empathy, and bullying, which necessitates educational innovations capable of engaging students’ emotional dimensions. Knowledge Gap While general character development is widely studied, research specifically addressing the implementation of compassion values within a love-based curriculum in elementary madrasahs remains limited. Aims This study aims to describe the application of compassion values within a love-based curriculum during learning processes at MI Ma’arif NU Sunan Drajat Lamongan. Results Qualitative descriptive analysis reveals that compassion is applied through teacher role models, positive daily habits, humanistic communication, and religious activities. This supportive school culture actively fosters empathy, caring, tolerance, cooperation, and respect among students. Supporting factors include a religious madrasah environment and teacher commitment, whereas primary obstacles involve differing student traits, familial influences, and unmonitored digital technology usage. Novelty This research specifically isolates compassion as a core structural component of love-based curricula, offering a unique and targeted perspective on humanistic learning in elementary Islamic education. Implications These findings provide a scientific contribution for educators seeking to cultivate harmonious learning environments, demonstrating that empathy-driven approaches build holistic social skills and positive peer interactions. Highlights Teacher role modeling and positive daily habits foster empathy and tolerance. Religious activities and humanistic communication build harmonious learning environments. Unmonitored digital technology usage and family backgrounds present implementation obstacles. Keywords Values Of Compassion; Humanistic Learning; Character Education; Moral Development; Islamic Education